Sustainability at University College Cork - Maria Kirrane; John O’Halloran; Mark Poland; Pat Mehigan (Journal of Sustainability Perspectives, 2023)
Abstract. UCC has been a leading institution for sustainability in Ireland and beyond for a number of decades. The approach at UCC has been to integrate sustainability within the operations, teaching, research and engagment activities of the University. Operationally UCC implements best practice in managing water consumption and disposal. Through our Green Campus programme, students, academic and professional services staff are actively engaged in environmental management on campus. Our water conservation efforts have followed the approach taken with energy management through our Saver Saves scheme. This scheme established Green Teams within Buildings and a revolving fund mechanism whereby teams were incentivised to reduce consumption and supported to implement projects specific to their individual setting. A major exercise to baseline water consumption was undertaken a number of years ago and drawing on these findings, specific projects have been implemented to improve efficiency. This paper will explore sustainability at UCC across operations, teaching, research and engagement with a specific focus on water. Keyword: Sustainability, energy consumption, single-use plastics, university